The Elegant Platelet: Signals Controlling Actin Assembly - Hartwig, John H.; Barkalow, Kurt; Azim, Anser; Italiano, Joe (Thrombosis and Haemostasis, 1999)
The function of the blood platelet is defined by its two physical states. The platelet is born in the first state, in long cytoplasmic extensions from megakaryocytes, as a small disc of reproducible structure having an elegant, actin-based cytoskeleton. At rest, the platelet circulates through the vasculature in this form. In the second state, in response to vascular damage, the platelet rapidly converts into its active form with filopodia and lamellipodia that derive from a remodeled actin skeleton and a massive assembly of new actin filaments. In the last two decades, we have begun to understand the structural basis for these two platelet states, the role of specific proteins that define the architecture of both shapes, and the proteins and signals that drive this conversion of shapes.